2011
DOI: 10.1074/jbc.m110.155622
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase-like-2 (LOXL2) Is a Major Isoform in Chondrocytes and Is Critically Required for Differentiation

Abstract: The lysyl oxidase family is made up of five members: lysyl oxidase (LOX) and lysyl oxidase-like 1-4 (LOXL1-LOXL4). All members share conserved C-terminal catalytic domains that provide for lysyl oxidase or lysyl oxidase-like enzyme activity; and more divergent propeptide regions. LOX family enzyme activities catalyze the final enzymatic conversion required for the formation of normal biosynthetic collagen and elastin cross-links. The importance of lysyl oxidase enzyme activity to normal bone development has lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 50 publications
3
38
0
1
Order By: Relevance
“…Consistently, the inhibition of LOXL2 activity promotes hDPSC differentiation to odontoblasts [173]. In contrast, LOXL2 expression increases significantly during chondrocyte differentiation, and its depletion abolishes chondrocyte differentiation [174].…”
Section: Loxl2 and Cellular Differentiationmentioning
confidence: 54%
“…Consistently, the inhibition of LOXL2 activity promotes hDPSC differentiation to odontoblasts [173]. In contrast, LOXL2 expression increases significantly during chondrocyte differentiation, and its depletion abolishes chondrocyte differentiation [174].…”
Section: Loxl2 and Cellular Differentiationmentioning
confidence: 54%
“…In fact, LOXL2 mRNA is markedly decreased in differentiated keratinocytes [63], and it has recently been shown that LOXL2 catalytic activity is dispensable for LOXL2-induced inhibition of keratinocyte differentiation, being the fourth scavenger receptor cysteine-rich domain in LOXL2 reportedly responsible for this function [64]. On the other hand, LOXL2 seems to be critically required for chondrocyte differentiation even though the detailed role of LOXL2 in chondrogenesis is not completely understood [65].…”
Section: Regulation Of Lysyl Oxidase Enzymes By Hypoxiamentioning
confidence: 98%
“…Thus, the oxidative stress of the surface •OH of Ao-Ti could enhance the mineralization of adherent cells to a greater extent than in the other samples. Despite the estimated oxidative stress on Ao-Ti, a previous study reported a great reduction in the oxidative stress on Ao-Ti as a consequence of oxygen diffusion into the culture medium by the invariable reaction between surface •OH and water (Iwai-Yoshida et al, 2012).…”
Section: Wurihan Et Al Oxidation Effect On Anodically Oxidized Titaniummentioning
confidence: 99%
“…Because bone is a natural biocomposite consisting of mineralized collagen fibers (Dvir et al, 2011;Gower, 2008), a cross-linked collagenous matrix is therefore essential, together with the expression of specific genes that induce ossification to ensure the hardness and elastic modulus of mineralized tissues (Paschalis et al, 2003;Wang et al, 2002). A recent study reports the expression of Loxl2 by prehypertrophic and hypertrophic chondrocytes during the chondrogenic phase of bone fracture healing (Iftikhar et al, 2011). Although the biological functions of the LOX family members in bone formation have not been fully elucidated, the cooperative interaction between osteogenic differentiation and oxidation of the collagen matrix is capable of mediating harder and stiffer in vitro mineralized tissue.…”
Section: Wurihan Et Al Oxidation Effect On Anodically Oxidized Titaniummentioning
confidence: 99%